Seqüelas em dentes permanentes após trauma nos predecessores decíduos e sua implicação clínica - Gondim, Juliana Oliveira [UNESP] (2011)
In regarding to the high prevalence of traumatic dental injuries in primary teeth and the possible disturbances on developing permanent successor germs, an early diagnosis and an adequate establishment of treatment planning are very important to minimize the damage caused by the trauma. Sequelaes can affect the coronal portion (white or yellow-brown discoloration associated or not with enamel hipoplasia, dilacerations of the crown), the root portion (dilaceration, duplication or cessation of root formation) or the whole successor permanent tooth (odontoma sequestration or disturbances of permanent successor eruption). The aim of this study is to make a literature review of the developmental disturbances of permanent teeth followed by traumatic injuries to theirs primary predecessors and to present cases reports to advise the dentists, their patients and parents about the damage that developing permanents teeth can undergo.